PERANCANGAN KAPAL BULK CARRIER 15000 DWT KECEPATAN 13 KNOT UNTUK PENGIRIMAN BATUBARA - PASIR BESI DENGANRUTE PELAYARAN TARAHAN (BANDAR LAMPUNG) - TANJUNG INTAN (CILACAP) - Jessica Novianly Siahaan, (2020)
Indonesia is a maritime country. A maritime country is a country which is most of its territory surrounded by ocean or sea. It means the ocean or sea are wider than the land. Indonesia is one of country that has the largest sea in the world. This makes Indonesia's territorial becomes to be a very strategic shipping lane. Indonesia is a country that is very rich in natural resources from Sumatra to Papua. Added by so many minerals of mining products such as coal, gold, nickel, copper, silver, natural gas, iron ore and many more of course it needs sophisticated distribution facilities which can create public welfare. But the fact is that we still have lack of marine fleets the number of marine fleets. Because the natural resources of mineral resources have not been fully utilized, mineral reserves in this country are abundant. Judging from these case, i would like to design a bulkcarrier which is suitable with the needs of the main transportation of marine fleets in Indonesia. Bulk Carrier is a type of commercial ship that is built to transport bulk loads such as coal, quartz sand, iron sand, metal ore, cement, limestone, grains such as wheat, corn, soybeans, etc. in cells or separate cargo cavities. The calculations main dimension use comparation method, and this method need 1 data of ship main dimension that all data base on Bureau Veritas (BV) France. Route of service Tarahan Bandar Lampung - Tanjung Intan Cilacap and service of speed 13 knots.The result calculation of preminary design had finded as: LOA: 131 m, Lpp: 125.61 m, B: 21.76 m, H: 11.18 m, T: 8.26, Cb: 0.79, Cm: 0.99, Cp: 0.80, Cw: 0.86.